Bahan pemutih gigi dengan sertifikat ADA/ISO (Tooth bleaching material with ADA/ISO certificate) - Asti Meizarini; Devi Rianti (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2005)
Bleaching of teeth for cosmetic reasons is a popular aspect of cosmetic dentistry because patients realize the aesthetical benefits of these products. The dentist as a clinician's practitioner must be knowledgeable of the products and their application techniques. Bleaching materials which are safe and effective are the ADA accepted or manufactured by those which have already haved ISO certificate. Dentist must have enough knowledge about in-office bleaching prescribed for home-use bleaching including their contra indication and side effects, to advise the patients and provide effective bleaching services.